Effect of Yoga and Naturopathy in a Patient with Uterine Fibroid - Y. Deepa; Mooventhan Aruchunan; T. Akshaya Mini; A. Akila (Journal of Integrated Health Sciences)
Uterine fibroids (UFs) are common in women during their reproductive age. A 40-year-old married woman was diagnosed with UF and underwent conventional treatment in March 2019. Her symptoms began with dysmenorrhea associated with bloating of the abdomen. Initially, she visited a private hospital, underwent ultrasonogram (USG) of the pelvis in a private diagnostic center, and the report suggests the presence of bulky uterus with fibroid and features of adenomyosis. Her physician advised to undergo a surgery, but she refused and thus visited our hospital. The patient underwent yoga and naturopathy intervention for the period of 11 days. The results of the study showed a reduction in the UF size from 27 mm × 22 mm to 22 mm × 18 mm in the 11 days of yoga and naturopathy intervention. Although the results are encouraging, it may vary because of a single case study. Hence, further well-planned clinical studies are suggested with a large sample size to validate our results.